GAMBARAN KESEGARAN JASMANI PADA REMAJA LAKI-LAKI DENGAN ANEMIA - Permaesih, Dewi; Rosmalina, Yuniar (PERSATUAN AHLI GIZI INDONESIA, 2004)
Physical fitness is needed for daily activities.The level of physical fitness could be recognizedthrough many measurement. Many factors influence the level of physical activity, include anemia.The purpose of the study is to find physical fitness level among anemia adult. A cross sectionaldesign was apllied in this study. This study site took place at Pondok Pesantren in Bogor,WestJava. Sample were student who stay in Pondok Pesantren. Data on anemia were identified fromresult of hemoglobin determination by cyanmethemoglobin method. Physical fitness scoremeasured from cardiovascular endurancece,muscle strength, flexibility, muscle endurance andbody composition. Univariate and bivariate were applied in this analysis. The result showed thatlevel of physical fitness index the sample 98,4 % in moderate level. The result biavariate analysisishowed relation between age and physical fitness index.Keywords: anemia, physical fitness, teenage